NORA10EI: A revised regional atmosphere‐wave hindcast for the North Sea, the Norwegian Sea and the Barents Sea. (6th January 2020) - Haakenstad, Hilde; Breivik, Øyvind; Reistad, Magnar; Aarnes, Ole J.
Abstract: NORA10EI, a new atmosphere and wave hindcast for the Norwegian Sea, the North Sea and the Barents Sea is presented. The hindcast uses ERA‐Interim as initial and boundary conditions and covers the period 1979–2017. The earlier NORA10 hindcast used ERA‐40 as initial and boundary conditions before September 2002 and operational analyses from the European Centre for Medium‐Range Weather Forecasts (ECMWF) in the continuation. This change in initial and boundary conditions may lead to non‐stationarities in bias and random errors, and it is a question of some concern whether this also leads to spurious trends. We investigate this by comparing the two hindcasts. We find only minor differences in the statistics of means and upper percentiles, but somewhat larger differences in the extremes (100‐year return values) of significant wave height and 10‐m winds. Generally, NORA10EI outperforms NORA10 in the ERA‐40 period (before September 2002) since ERA‐Interim outperforms ERA‐40. Conversely, NORA10 outperforms NORA10EI after 2006, since the operational ECMWF analyses here outperform ERA‐Interim. Years 2002–2006 is a transition period with minor differences between the NORA10 and NORA10EI where the resolution of ERA‐Interim is lower than that of the ECMWF analyses, but its physics are from a more recent model (2006). An important finding is that the regional hindcasts appear quite insensitive to changes in the host reanalysis with no statistically significant differences in mean and upper percentile trends of wind speed and wave height. A comparison of four polar low cases confirms that using ERA‐Interim as host reanalysis yields a slightly better representation of evolution and intensity of polar lows than NORA10 in the ERA‐40 period and the opposite after 2006. Abstract : Overview of the model domain with offshore and coastal stations. The domains used for trend analysis are coloured. The domains are numbered 1–4 from south to north.